Control of randomly scattered surface plasmon polaritons for multiple-input and multiple-output plasmonic switching devices - Wonjun Choi (Nature Portfolio, 2017)
Losses of bandwidth are inevitable when interfacing between optical and electronic components. Here the authors present a switching device consisting of a two-dimensional disordered array of nanoholes that can potentially transfer information about 40 times faster than conventional switching devices.